Pedunculopontine nucleus stimulation improves akinesia in a Parkinsonian monkey. - Jenkinson, E; Nandi, D; Miall, R; Stein, J; Aziz, T (2004)
We have studied the effects of stimulating the pedunculopontine nuclei through a fully implanted macroelectrode with a s.c. implantable pulse generator whose parameters can be programmed telemetrically, in a macaque before and after inducing Parkinsonian akinesia with MPTP. Our results show that in the normal monkey high frequency stimulation of the pedunculopontine nuclei reduces motor activity while low frequency stimulation increases it significantly over baseline. After making the monkey Parkinsonian with MPTP, unilateral low frequency stimulation of the pedunculopontine nuclei led to significant increases in activity. These results suggest that pedunculopontine nuclei stimulation could be clinically effective in treating advanced Parkinson's disease and other akinetic disorders.